Does patients' age predict their clinical outcomes following non-infectious epiglottitis? A systematic review. - Alaa Safia; Uday Abd Elhadi; Rabie Shehadeh; Raed Farhat; Majd Asakly; Nidal El Khatib; Ashraf Khater; Taiser Bishara; Saqr Massoud; Shlomo Merchavy (PLoS ONE)
Background Non-infectious epiglottitis, an infrequent but significant condition, presents challenges in airway management and treatment due to its potential for rapid progression. Objective To analyze differences in clinicodemographic characteristics, management strategies, and clinical outcomes between pediatric and adult cases of non-infectious epiglottitis. Methods A systematic search of four databases identified 57 patient records, all diagnosed with non-infectious epiglottitis. Children (<18 years) were compared to adults (≥18 years). Differences in clinicodemographic characteristics, management strategies, and clinical outcomes were analyzed. Outcomes included intubation, complications, and intensive care unit (ICU) admission. Risk factors of these outcomes were identified through uni- and multi-variable logistic regression analyses. Results Twenty-three children and 34 adults were analyzed. The presentation with stridor (56.52% vs. 14.7%), drooling (56.52% vs. 26.47%), cyanosis (17.39% vs. 0%), and sternal retraction (13.04% vs. 0%) was more common among children. Prior vaccination was evident in only 5 pediatric cases. The etiology of epiglottitis was similar across groups. Children had significantly higher chances of receiving epinephrine (34.78% vs. 8.82%), undergoing intubation (82.60% vs. 20.58%), being admitted to the ICU (56.52% vs. 17.64%), and having complications (47.82% vs. 14.70%), compared to adults. In the multivariate regression model, pediatric age was a risk factor for intubation (p = 0.015) and ICU admission (p = 0.040), while foreign body ingestion (p = 0.039) and dyspnea (p = 0.014) were predictors of intubation and complications, respectively. Conclusions The study highlights the necessity for age-specific management strategies in non-infectious epiglottitis. Understanding the distinct clinical presentations and responses in different age groups can lead to improved patient care.